The impact of lipid accumulation product (LAP) and visceral adiposity index (VAI) on clinical, hormonal and metabolic parameters in lean women with polycystic ovary syndrome - YILDIZHAN, BEGÜM; ANIK İLHAN, GÖKÇE; PEKİN, TANJU (TAYLOR & FRANCIS LTD, 2019)
This study was performed to assess the impact of lipid accumulation product (LAP) and visceral adiposity index (VAI) on clinical, hormonal, and metabolic parameters in lean women with PCOS. Retrospective analysis of 120 consecutive lean PCOS subjects was performed. Subjects were divided into two groups according to HOMA-IR, as IR + and IR-. A HOMA-IR value above 2.5 was used to indicate IR. Clinical, hormonal and metabolic parameters were compared between the two groups. Correlations between LAP and VAI and clinical, hormonal, metabolic features in women PCOS were analyzed. One hundred twenty lean PCOS subjects were enrolled, of which 39 were insulin resistant. Comparison of group means showed significantly higher values for TG levels, FAI, FGS, TG/HDL-c, TyG, LAP, and VAI indexes and lower values for glucose/insulin ratio and QUICKI in the IR + group. LAP and VAI were both found to be positively correlated with each other and with WC, FAI, FGS, TG, TC levels, lipid ratios, TyG index, and HOMA-IR and negatively correlated with Glucose/Insulin ratio, QUICKI, and HDL-c in lean women with PCOS. LAP and VAI may be promising in early identification of IR and cardiometabolic risk and may be useful for the assessment of hyperandrogenism in lean women with PCOS.
Keywords: Polycystic ovary syndrome; lean; insulin resistance; lipid accumulation product; visceral adiposity index; INSULIN-RESISTANCE; CARDIOVASCULAR RISK; SENSITIVITY; POPULATION; PREDICTORS; SEVERITY; MARKERS